PENGARUH KUANTITAS KAPUR TOHOR TERHADAP MASA SIMPAN TOMAT (Lycopersicum esculentum Mill.) - Sucipto, Christhoperus Vincent; Andrianto, Kurniawan; Handoko, Yoga Aji (Jurnal Sains dan Teknologi Pangan, 2021)
The fruit that has been harvested is still carrying out the process of metabolism and respiration which causes the overhaul of the nutrients in the fruit which results in a degeneration process so that the fruit is quickly damaged. Tomato (Lycopersicum esculentum Mill.) Is a horticultural plant that has many benefits. The high rate of tomato damage during postharvest is one of the problems faced in meeting consumer expectations. Post-harvest handling is an important thing that needs to be taken into account by all actors in a supply chain until it reaches consumers, so that the quality of the deterioration in the quality of vegetables can be controlled. Therefore, the purpose of this study was to determine the handling and application of the fastest post-harvest activities for tomato plants using quicklime treatment. The characteristics of quicklime which can absorb CO2 at the time of respiration of tomatoes occur. With the increasing quantity of quicklime given, the more effective it will be in absorbing CO, so that this lime has a good adsorption ability of CO2 gas. The parameters observed in this research were weight loss, color, texture, and tomato damage